2012
DOI: 10.1088/0031-9155/57/14/4461
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the influence of detector density on dosimeter response in non-equilibrium small photon fields

Abstract: The impact of density and atomic composition on the dosimetric response of various detectors in small photon radiation fields is characterized using a 'density-correction' factor, F(detector), defined as the ratio of Monte Carlo calculated doses delivered to water and detector voxels located on-axis, 5 cm deep in a water phantom with a SSD of 100 cm. The variation of F(detector) with field size has been computed for detector voxels of various materials and densities. For ion chambers and solid-state detectors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
182
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(197 citation statements)
references
References 20 publications
(38 reference statements)
14
182
1
Order By: Relevance
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 . Monte Carlo simulations have shown that the magnitude of overresponse is proportional to the mass density of the material in the volume of interest, with a larger overresponse determined for a voxel of the same size in a radiation beam for diamond than for silicon in a 5 mm field for 15 MV (38) . Similarly, air‐filled ionization chambers will show an underresponse compared to water, due to the low density of air compared with water in the sensitive volume.…”
Section: Discussionmentioning
confidence: 99%
“…The dose perturbation effect is also minimal with the PSD, considering it has a physical density of 1.0 5 g/cm (39) . One major advantage of PSD over film is its instantaneous readout, which was favorable for clinical dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements are challenging, and are fundamentally linked to the physics of small fields. Unlike traditional large fields, electronic equilibrium breaks down as the radiation field size drops below the range of the secondary electrons, invalidating the Bragg‐Gray conditions 8 , 9 . Source occlusion also takes place at small fields, resulting in a decrease in the dose deposited (4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation